Strategi Industri Bisnis PT Citra Van Titipan Kilat melalui Electronic Customer Relationship Management - Janudin Janudin; Arief Setiawan Putra (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The rapid development of digital technology has encouraged logistics and courier service companies to adopt customer-oriented strategies to maintain competitiveness. Electronic Customer Relationship Management (E-CRM) has emerged as a strategic approach to improve customer satisfaction, loyalty, and business performance through integrated information systems. This study aims to analyze the implementation of E-CRM as an industrial business strategy at PT Citra Van Titipan Kilat. The research employs a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and documentation related to customer service processes, complaint handling, and customer data management. The analysis focuses on E-CRM dimensions, including customer identification, interaction, and customization. The results show that the implementation of E-CRM at PT Citra Van Titipan Kilat contributes positively to improving service efficiency, strengthening customer relationships, and increasing customer loyalty. However, several challenges remain, such as system integration limitations and the need for continuous employee training. This study concludes that E-CRM plays a strategic role in supporting business sustainability and competitiveness in the logistics industry. The findings are expected to provide practical implications for similar service-based companies in optimizing E-CRM implementation.